The study on venture investment evaluation based on linguistic variables for Chinese case - Liu, Peide (Journal of Business Economics and Management, 2011)
The venture investment evaluation plays a very important role in the venture investment operation process. The goal of the paper is development of evaluation index systems and evaluation methods for venture investment. Firstly, the evaluation index systems of venture investment project are constructed in accordance with China’s practical situation. Then evaluation models have been presented. In the models, operational laws of linguistic variables and distance of two linguistic variables are defined; and a single objective optimization model is constructed by maximizing deviation method to get the objective weights of indexes, and alternatives are ranked by TOPSIS and grey relation methods respectively. Finally, a numerical example is given to illustrate the evaluation procedures of two approaches. The case shows that two different approaches get the same result, but TOPSIS is simpler apparently. Article in English. Įmonės investicijų vertinimo tyrimas Kinijos pavyzdžiu Santrauka. Šiame straipsnyje analizuojama, kokią įtaką turi įmonės investicijų vertinimas visam investavimo procesui. Šiam tikslui pasiekti autorius pasirinko vertinimo indeksų sistemą ir investicijų vertinimo rizikos metodus. Pirmąjį pasirinktą instrumentą, t. y. vertinimo indeksų sistemą, autorius naudoja analizuodamas ir atlikdamas Kinijoje vykdomų investicinių projektų vertinimo tyrimą. Kitus tyrimo instrumentus ir matematinius metodus, tokius kaip TOPSIS, Grey metodas ir pan., taiko apibendrindamas gautus rezultatus. Reikšminiai žodžiai: TOPSIS, Grey metodas, santykinė reikšmė, investicijos.